(untitled) (ModaPalavra e-periódico, 2023)
This article aims to understand how creation and resistance are connected in the production of Fernanda Yamamoto, a Brazilian stylist recognized nationally and internationally, focused on the 52nd edition of São Paulo Fashion Week, which took place in November 2021. The production process of information for the research resulted from the immersion in the artist’s studio in the period that preceded the fashion show, and were recorded in a field diary. Discussions on thehyperfashion system woven by Gilles Lipovetsky, added to the ideas of the architectonics of artistic creation by Mikhail Bakhtin, among other contributions, underlie the analyzes that intertwine Fernanda Yamamoto’s creation with the field of fashion and the artistic field. The ways of creating, making and showing a collection mark the ethical-aesthetic-political positioning of the artist and her team in relation to participation in the international fashion week in São Paulo and, from a broader perspective, to the great hyperfashion context.